Explanations for less small fibre neuropathy in South Asian versus European subjects with type 2 diabetes in the UK. Issue 7 (9th August 2018) - Fadavi, Hassan; Tavakoli, Mitra; Foden, Philip; Ferdousi, Maryam; Petropoulos, Ioannis N.; Jeziorska, Maria; Chaturvedi, Nishi; Boulton, Andrew J.M.; Malik, Rayaz A.; Abbott, Caroline A.
Abstract: Background: Low foot ulcer risk in South Asian, compared with European, people with type 2 diabetes in the UK has been attributed to their lower levels of neuropathy. We have undertaken a detailed study of corneal nerve morphology and neuropathy risk factors, to establish the basis of preserved small nerve fibre function in South Asians versus Europeans. Methods: In a cross‐sectional, population‐based study, age‐ and sex‐matched South Asians ( n = 77) and Europeans ( n = 78) with type 2 diabetes underwent neuropathy assessment using corneal confocal microscopy, symptoms, signs, quantitative sensory testing, electrophysiology and autonomic function testing. Multivariable linear regression analyses determined factors accounting for ethnic differences in small fibre damage. Results: Corneal nerve fibre length (22.0 ± 7.9 vs. 19.3 ± 6.3 mm/mm 2 ; P = 0.037), corneal nerve branch density (geometric mean (range): 60.0 (4.7‐246.2) vs. 46.0 (3.1‐129.2) no./mm 2 ; P = 0.021) and heart rate variability (geometric mean (range): 7.9 (1.4‐27.7) vs. 6.5 (1.5‐22.0); P = 0.044), were significantly higher in South Asians vs. Europeans. All other neuropathy measures did not differ, except for better sural nerve amplitude in South Asians (geometric mean (range): 10.0 (1.3‐43.0) vs. 7.2 (1.0‐30.0); P = 0.006). Variables with the greatest impact on attenuating the P value for age‐ and HbA1C ‐adjusted ethnic difference in corneal nerve fibre length ( P = 0.032) were pack‐years smoked ( P = 0.13), BMI ( P = 0.062) and triglyceride levels (P = 0.062). Conclusions: South Asians have better preserved small nerve fibre integrity than equivalent Europeans; furthermore, classic, modifiable risk factors for coronary heart disease are the main contributors to these ethnic differences. We suggest that improved autonomic neurogenic control of cutaneous blood flow in Asians may contribute to their protection against foot ulcers.